Melanins: Skin Pigments and Much More—Types, Structural Models, Biological Functions, and Formation Routes. (18th March 2014) - Solano, F.
Abstract : This review presents a general view of all types of melanin in all types of organisms. Melanin is frequently considered just an animal cutaneous pigment and is treated separately from similar fungal or bacterial pigments. Similarities concerning the phenol precursors and common patterns in the formation routes are discussed. All melanins are formed in a first enzymatically-controlled phase, generally a phenolase, and a second phase characterized by an uncontrolled polymerization of the oxidized intermediates. In that second phase, quinones derived from phenol oxidation play a crucial role. Concerning functions, all melanins show a common feature, a protective role, but they are not merely photoprotective pigments against UV sunlight. In pathogenic microorganisms, melanization becomes a virulence factor since melanin protects microbial cells from defense mechanisms in the infected host. In turn, some melanins are formed in tissues where sunlight radiation is not a potential threat. Then, their redox, metal chelating, or free radical scavenging properties are more important than light absorption capacity. These pigments sometimes behave as a double-edged sword, and inhibition of melanogenesis is desirable in different cells. Melanin biochemistry is an active field of research from dermatological, biomedical, cosmetical, and microbiological points of view, as well as fruit technology.